Voltage controlled Bi-mode resistive switching effects in MnO2 based devices. (18th December 2017) - Hu, P; Wu, S X; Wang, G L; Li, H W; Li, D; Li, S W
Abstract: In this paper, the voltage induced bi-mode resistive switching behavior of an MnO2 thin film based device was studied. The device showed prominent bipolar resistive switching behavior with good reproducibility and high endurance. In addition, complementary resistive switching characteristics can be observed by extending the voltage bias during voltage sweep operations. The electrical measurement data and fitting results indicate that the oxygen vacancies act as defects to form a conductive path, which is connective or disrupted to realize a low resistive state or a high resistive state. Changing the sweep voltage can tune the oxygen vacancies distribution, which will achieve complementary resistive switching.